The South African criminal justice : does S v Eadie 2002 (1) SACR 663 (SCA) create a battering ram in rejection of the defence afforded a battered woman or recourse of victims turned accused? - Carstens, Pieter Albert, 1960- (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.